Climate change in Chinese rural village: is the community aware? A case study in Cuandixia, using the Photovoice method. Issue 4 (7th November 2016) - Dupre, Karine; Dai, Linlin; Xu, Bixia
Abstract : Purpose: In recent Chinese history, rural villages have suffered extensive depopulation due to the intensive urbanisation of the country. In the early 1990s, the rediscovery of villages for tourism purposes caused a change in approach to conservation policies and village management. Today, villages are subjected to climate change with mass tourism as a contributing factor. The purpose of this paper is to evaluate whether the village community is climate change aware and to identify best practises for it. Design/methodology/approach: In this case study, the authors adopted a visual research technique called Photovoice. It is a research method which combines preliminary data collection and initial analysis processes. The main goals of adopting Photovoice are to enable community members to record and reflect their community's strengths and concerns, to promote dialogue and knowledge exchange among community members regarding critical local social or environmental issues through small group discussion, and to report to policymakers. Findings: This research demonstrated that both visitors and hosts shared common thoughts on tourism interests, impacts and current actions regarding climate change. Age, level of education or origin did not interfere and it shows a common awareness regarding the effects of climate change. It confirms the structural assumption that local and expertise knowledge are complementary. Originality/value: At a time when awareness of climate change is affecting almost every debate concerning development strategies, future planning, governance and action implementations, very little has been written on the climate change impact on villages from a community perspective. Even less has been researched on what are called "urban rural villages", that are villages located at the close periphery of a large urban agglomerations or cities in China.